Determining power training needs using the force-velocity profile (imbalance) in elite female volleyball using different vertical jump - Joksimović Marko; Badau Dana; Tawfeeq Rebaz B.; Eler Nebahat; Muntean Raul Ioan; Badau Adela; Plevnik Matej (Balneo and PRM Research Journal, 2025)
This study aimed to evaluate the Force-Velocity (Fv) profile of elite female volleyball players during the Squat Jump and Countermovement Jump to define the Fv profile of female athletes based on strength, power, and individual mechanical characteristics. The goal was to enhance training efficiency and improve performance in ballistic movements. For this study, we recruited 12 elite female volleyball players from the Montenegro U19 national team. The Fv profile was assessed in two types of muscle contractions: the Squat Jump (concentric contraction) and the Countermovement Jump (eccentric-concentric contraction) to determine Fv imbalance. First, the height of the jump was measured in the Squat Jump, followed by the Countermovement Jump. After that, the Fv profile was analyzed under both contraction types to assess potential imbalances. The results showed an Fv imbalance of 24.93% during the concentric muscle contraction and 29.71% during the eccentric-concentric muscle contraction. Based on these findings, it is suggested that training should prioritize enhancing strength capabilities while simultaneously addressing Fv imbalances. Reducing theoretical Fv imbalance could serve as a supplementary component of training to improve overall physical performance.
Keywords: multi-joint movements; jumping performance; muscle contraction; mechanical characteristics; ballistic movements; imbalance; physical performance